DIGITAL LITERACY AMONG THE ELDERLY: LITERATURE REVIEW AND IMPLEMENTATION IN COMMUNITY SERVICE - Ade Risna Sari; Moh. Imron Rosidi; Andi Fitriani Djollong (JOURNAL OF COMMUNITY DEDICATION, 2023)
The literature review on digital literacy among the elderly highlights the barriers faced by this age group in adopting digital technology, including access, understanding, and confidence. The implementation of the community service program shows concrete steps to improve the digital literacy of the elderly, such as hands-on training, partnership building, awareness campaigns, and the creation of a supportive physical environment. Periodic evaluation, documentation of results, and cross-sector collaboration are key in maintaining the sustainability of these programs. The implication of this study is that efforts to improve digital literacy among older adults have the potential to have a positive impact on older adults' quality of life and enable them to stay connected to the digital world more effectively.